AN ANALYSIS OF STUDENTS’ ERRORS IN WRITING RECOUNT TEXT - Anugrah Mustika Maizu; Jamiluddin Jamiluddin; Agussatriana Agussatriana (Tadulako University, 2022)
This research aims to find out the grammatical errors and the dominant error written by the tenth-grade students of SMA Karuna Dipa Palu in the academic year 2021/2022 in writing recount text. The researchers used the descriptive qualitative design. The subject of this research was all the tenth-grade students of SMA Karuna Dipa Palu which consisted of 32 students. In collecting the data, the researchers used test as the instrument. The researchers analyzed the data by using error analysis. The result of the research showed that the students made 412 errors in their recount texts which are classified into: simple past tense (34.7%), preposition (6.1%), pronoun (3.9%), spelling (10.7%), and punctuation (44.7%). The dominant error is punctuation. The dominant errors occurred because the students pay less attention to the use of good and correct punctuation. They are apathetic to the use of punctuation.